Modulatory effect of mild inflammation on tau phosphorylation in a human tau mouse model of Alzheimer's disease - Barron, Matthew (2018)
Alzheimer’s disease (AD) is the most common form of dementia and involves the pathological hyperphosphorylation and aggregation of the microtubule associated protein tau. Aetiological evidence, and evidence from post-mortem studies, suggests neuroinflammation to be an early mechanistic driver of AD. In murine tau models, systemic inflammation induced by either chronic or acute lipopolysaccharide (LPS) administration has been reported to be a strong inducer of early tau pathology through augmenting tau hyperphosphorylation. However, the method by which LPS has been utilised to model inflammation in these studies has not always been representative of the underlying mild inflammation occurring in AD. For example, following chronic LPS administration, rapid tolerance occurs which is not representative of AD. While acute LPS administration results in a rapid pro-inflammatory response, the doses which have generally been utilised are more analogous with sepsis rather than the underlying inflammatory response observed in AD. This thesis is aimed at furthering clarifying the contribution of systemic inflammation to early tau pathology through systemic administration of low doses of LPS in the hTau model. The hTau model is thought to be the most relevant AD tau model for the expression of all 6, non-mutated, human tau isoforms on a murine tau (mTau) knockout (KO) background. However, hTau mice are associated with systemic pathologies and an increased ratio of 3R:4R tau isoforms which is not representative of AD. As the systemic pathologies are linked to the KO of mTau which consists solely of 4R tau isoforms, hTau mice were bred on a partial mTau background in the hope to avert the systemic pathologies, improve the isoform ratio and conserve the development of tau pathology. Heterozygous mTau expression in hTau/mTau+/- mice resulted in ablation of systemic pathologies, an increase in 4R tau isoforms and augmented tau hyperphosphorylation compared to hTau/mTau-/- mice, indicating the model ideal for understanding early pathological tau alterations. To determine the effect mild inflammation might have on early tau pathology in AD, tau phosphorylation, localisation and aggregation were assessed after 0, 100, 250 and 330 µg/kg (i.v.) LPS administration in 3 month old hTau/mTau+/- and hTau/mTau-/- mice during the height of the pro-inflammatory response at 4h following administration. LPS administration resulted in dose-dependent decreases in the pre-tangle associated phosphorylation epitope; pS202 in both genotypes while the post-tangle associated epitope; pS396/404 levels were selectively decreased in hTau/mTau+/- mice. On the other hand, LPS did not induce tau aggregation. To determine whether less immediate effects on tau pathology occurred, tau pathology was assessed 24h following 250 µg/kg (i.v.) LPS administration in hTau/mTau+/- mice. Tau dephosphorylation persisting at both pS202 and pS396/404 epitopes at this time point. These results suggest that systemic inflammation might play a beneficial role on tau pathology in AD.